Application of Enzyme Functional Feed as a Supplement to the Growth of Silver Pompano (Trachinotus Blochii) in Floating Net Cage, Pangandaran District - Rita Rostika; Aulia Andhikawati; Ajeng Amirah Yasmin; Roffi Grandiosa (International Journal Labs, 2023)
The study aims to determine the effect of applying papain enzyme to functional enzyme feed (PFE) with optimal doses to produce the highest growth of pomfret in floating net cages, Pangandaran Regency. This research was conducted from September 2022 to December 2022 with 60 days of fish rearing. The method used in this study was a completely randomized design (CRD) with five treatments and 3 replications. The treatments were A (artificial feed containing 5% papain enzyme in PFE), B (artificial feed containing 3.75% papain enzyme in PFE), C (artificial feed containing 2.5% papain enzyme in PFE), D (artificial feed containing 1.25% papain enzyme in PFE), and E (control). The effect of each treatment was tested by analysis of variance (ANOVA) F test at a 5% test interval, if there was a significant difference it was continued with Duncan's multiple range test. The parameters observed in this study included fish survival (SR), Daily Growth Rate (LPH), Feeding Efficiency (EPP), and water quality at the study site. The results obtained from this study were the use of functional enzyme feeds to increase fish survival (SR), Daily Growth Rate (LPH), Feeding Efficiency (EPP), and water quality at the study site. The highest growth value in this study was in treatment A (artificial feed containing 5% papain enzyme in PFE) with LPH of 3.25 ± 0.112 %, EPP of 80 ± 6.164 %, SR of 100%, and the range of water quality in the location research namely dissolved oxygen (DO) levels ranging from 5.6 to 6.7 mg/L, temperature ranging from 27 to 29 o C, pH ranging from 7 to 8, and salinity ranging from 32 to 34 ppt.